Glaucoma Features in an East African Population: A 6-Year Cohort Study of Older Adults in Nakuru, Kenya. Issue 5 (May 2018) - Bastawrous, Andrew; Mathenge, Wanjiku; Buchan, John; Kyari, Fatima; Peto, Tunde; Rono, Hillary; Weiss, Helen A.; Macleod, David; Foster, Allen; Burton, Matthew J.; Kuper, Hannah
Abstract : Purpose: Glaucoma is a leading cause of blindness in people of African descent. Minimal data is available from African population–based cohort studies. The primary aims of this study were to describe the normative distribution of glaucoma features to enable glaucoma classification and to assess risk factors for those with glaucoma at follow-up among people aged 50 years and above in Kenya. Materials and Methods: Random cluster sampling with probability proportionate to size was used to select a representative cross-sectional sample of adults aged 50 years and above in 2007 to 2008 in Nakuru District, Kenya. A 6-year follow-up was undertaken in 2013 to 2014. Comprehensive ophthalmic examination included visual acuity, digital retinal photography, visual fields, intraocular pressure, optical coherence tomography, and independent grading of optic nerve images. We report glaucoma features, prevalence and predictors for glaucoma based on the International Society for Geographical & Epidemiological Ophthalmology (ISGEO) criteria. Measures were estimated using a Poisson regression model and including inverse-probability weighting for loss to follow-up. Results: At baseline, 4414 participants aged 50 years and above underwent examination. Anterior chamber optical coherence tomography findings: mean anterior chamber angle of 36.6 degrees, mean central corneal thickness of 508.1 μm and a mean anterior chamber depth of 2.67 mm. A total of 2171 participants were examined at follow-up. The vertical cup to disc ratio distribution was 0.7 and 0.8 at the 97.5th and 99.5th percentiles, respectively. A total of 88 (4.3%, 95% confidence interval, 3.5%-5.9%) of participants at follow-up had glaucoma consistent with ISGEO criteria. A relative afferent pupillary defect and raised intraocular pressure were associated with the diagnosis. Conclusions: Glaucoma is a public health challenge in low-resource settings. Research into testing and treatment modalities in Africa is needed.